An exploration of comorbid depression among female victims of intimate partner violence with posttraumatic stress disorder - Nixon, Reginald D.V. (2004)
BACKGROUND AND METHODS: Factors contributing to posttraumatic stress disorder (PTSD) and comorbid major depression (MDD) were investigated among female victims of intimate partner violence (IPV). RESULTS: High levels of PTSD (75% of the sample) and MDD (54% of the sample) were observed. Individuals with both PTSD and MDD reported significantly greater levels of PTSD and depression symptoms than individuals with either PTSD alone or without major psychopathology. Individuals with comorbid PTSD and MDD had more maladaptive depressogenic cognitive styles than individuals without PTSD. The three groups were comparable in terms of pre-abuse mental health, childhood trauma history, and relationship violence variables and injuries. Maladaptive schemas did not contribute to the identification of comorbidity caseness, whereas PTSD severity and prior trauma did. Psychological aggression by an abuser and PTSD severity accounted for 52% of the variance in depressive symptoms. LIMITATIONS: Cross-sectional design and lack of trauma-specific cognitive measures. CONCLUSIONS: The findings confirm that comorbid PTSD and MDD is common among IPV victims. The mechanisms that contribute to comorbid depression, however, are unclear, and prospective studies are necessary to delineate the roles that psychological abuse, PTSD severity and prior trauma experiences may have in the development of depression following IPV.